Influences of Price, Promotion, and Service quality on Communities’ Interest in Choosing Vocational High School - Kasmad Kasmad; Masran Mustakim; Denok Sunarsi (Journal of Educational Science and Technology (EST), 2020)
This study aims at investigating the influence of price, promotion, and service quality on the societies’ interest to register their children in the Vocational High School in South Tangerang. This study employed the explanatory research method by involving 96 respondents. Data were analyzed using statistical analysis methods including regression test, correlation test, determination test, and hypothesis test. The findings showed that price significantly influences the communities’ interest (32,4%) and the hypothesis test got the significance level at 0.000 < 0.05. Promotion is significantly influential at 36.9% and the hypothesis test showed a score of 0.000 < 0.05. The quality of the service is simultaneously significantly influential on the interest in Vocational High School at 30.2 % and the hypothesis test shows the significance score of 0,000 < 0,05. This indicates that price, promotion, and service quality can trigger societies’ interest to register their children into the Vocational High School. Thus, these three components can be solutions to increase the number of students in Vocational High Schools.